A dança contemporânea do Ballet Stagium e do Teatro de São Paulo: experiências artístico-políticas no Brasil (1971-1978) - Veloso Junior, Carlos De Moura [UNIFESP] (2020)
The dissertation main objective was to analyze the political-artistic experiences of the dance companies Ballet Stagium and Teatro de Dança de São Paulo from 1971 to 1978.Both artistic groups, during the military dictatorship period in Brazil, saw in the contemporary dance art, the possibility of manifesting themselves politically through the choreographic compositions production and presentation that brought in their thematic social and political nature plots. Therefore, through the description and analysis of the choreographic compositions Diadorim (1972), Dona Maria I: a rainha louca (1974), Quebradas do Mundaréu (1975), Allegro Ma Non Troppo (1975) and Kuarup (1977) and reports of certain artists who danced in these companies during this period, it became possible to understand how in the middle of the military regime, two artistic groups acted politically, using contemporary dance shows as a political manifestation form. During the research process we also realized that the press had a fundamental role for the circulation of information about the Ballet Stagium and the Teatro de Dança de São Paulo, so we aimed to start in this dissertation a study that sought to bring criticism and written newspaper articles during the seventies about the analyzed shows, and then verify how the choreographic proposals from both companies were disseminated to the population through the press.